Masalah Pendayagunaan Wakaf Tunai Bidang Pendidikan Pada Baitul Maal Hidayatullah Surabaya - Abdurrofiil Ali; Irham Zaki (Universitas Airlangga, 2017)
A nation with moslem majority has a potential funding and its collection has a solutive way in educational field. Baitul. The researcher chooses cash wakaf because there is still a little researcher studies about cash wakaf and choosing Baitul Maal Hidayatullah Surabaya is because this institution is still rarely chosen, especially the one in Surabaya. The research uses qualitative approach. The informant is decided by using purposive sampling, they are nadzhir, wakif and mauquf ‘alaih with six number of total informants. The analyzing technique used is qualitative model analysis by Yin.The result of the research concludes that utilizing cash wakaf funding done by BMH is distributed to all BMH programs, one of which is in Educational field. The program of cash wakaf in BMH can be achieved by the success of utilizing cash wakaf in educational field.